Mums 4 Mums: structured telephone peer-support for women experiencing postnatal depression. Pilot and exploratory RCT of its clinical and cost effectiveness - McKenzie-McHarg Kirstie; Sembi Sukhdev; Barlow Jane; Caramlau Isabela; McCabe Chris (Trials, 2011)
Abstract Background Postnatal depression (PND) can be experienced by 13% of women who give birth, and such women often exhibit disabling symptoms, which can have a negative effect on the mother and infant relationship, with significant consequences in terms of the child's later capacity for affect regulation. Research has shown that providing support to mothers experiencing PND can help reduce their depressive symptoms and improve their coping strategies. The Mums4Mums study aims to evaluate the impact of telephone peer-support for women experiencing PND. Methods/Design The study design adopts the MRC framework for the development and evaluation of complex interventions. Health visitors in Warwickshire and Coventry Primary Care Trusts are screening potential participants at the 8-week postnatal check using either the Edinburgh Postnatal Depression Scale (EPDS > = 10) or the three Whooley questions recommended by NICE (http://guidance.nice.org.uk/CG45). The Mums4Mums telephone support intervention is being delivered by trained peer-supporters over a period of four months. The primary outcome is depressive symptomatology as measured by the Edinburgh Postnatal Depression Scale. Secondary outcomes include mother-child interaction, dyadic adjustment, parenting sense of competence scale, and self-efficacy. Maternal perceptions of the telephone peer-support are being assessed using semi-structured interviews following the completion of the intervention. Discussion The proposed study will develop current innovative work in peer-led support interventions and telecare by applying existing expertise to a new domain (i.e. PND), testing the feasibility of a peer-led telephone intervention for mothers living with PND, and developing the relationship between the lay and clinical communities. The intervention will potentially benefit a significant number of patients and support a future application for a larger study to undertake a full evaluation of the clinical and cost effectiveness of telephone based peer-support for PND. Trial registration ISRCTN: ISRCTN91450073. The study has received a major funding grant from National Institute for Health Research (NIHR) (UK) - Research for Patient Benefit (RfPB) programme (ref: PB-PG-0407-13232).